Bile Acid Receptor Activation Modulates Hepatic Monocyte Activity and Improves Nonalcoholic Fatty Liver Disease - McMahan, Rachel H.; Wang, Xiaoxin X.; Cheng, Lin Ling; Krisko, Tibor; Smith, Maxwell; El Kasmi, Karim; Pruzanski, Mark; Adorini, Luciano; Golden-Mason, Lucy; Levi, Moshe; Rosen, Hugo R. (The Journal of biological chemistry, 2013)
Nonalcoholic fatty liver disease (NAFLD) affects a large proportion of the American population. The spectrum of disease ranges from bland steatosis without inflammation to nonalcoholic steatohepatitis and cirrhosis. Bile acids are critical regulators of hepatic lipid and glucose metabolism and signal through two major receptor pathways: farnesoid X receptor (FXR), a member of the nuclear hormone receptor superfamily, and TGR5, a G protein-coupled bile acid receptor (GPBAR1). Both FXR and TGR5 demonstrate pleiotropic functions, including immune modulation. To evaluate the effects of these pathways in NAFLD, we treated obese db/db mice with a dual FXR/TGR5 agonist (INT-767) for 6 weeks. Treatment with the agonist significantly improved the histological features of nonalcoholic steatohepatitis. Furthermore, treatment increased the proportion of intrahepatic monocytes with the anti-inflammatory Ly6Clow phenotype and increased intrahepatic expression of genes expressed by alternatively activated macrophages, including CD206, Retnla, and Clec7a. In vitro treatment of monocytes with INT-767 led to decreased Ly6C expression and increased IL-10 production through a cAMP-dependent pathway. Our data indicate that FXR/TGR5 activation coordinates the immune phenotype of monocytes and macrophages, both in vitro and in vivo, identifying potential targeting strategies for treatment of NAFLD. Background: The bile acid receptors FXR and TGR5 have pleiotropic functions, including immune modulation. Results: Treatment of a murine model of nonalcoholic fatty liver disease (NAFLD) with a dual FXR/TGR5 agonist decreased intrahepatic inflammation and altered the immune phenotype of monocytes. Conclusion: Bile acid receptor activation improves NAFLD. Significance: These results identify potential targeting strategies for treatment of NAFLD.